Toxic ignorance and right-to-know in biomonitoring results communication: a survey of scientists and study participants - Altman Rebecca; Brown Phil; Brody Julia; Morello-Frosch Rachel; Rudel Ruthann A; Pérez Carla (BMC, 2009)
Abstract Background Exposure assessment has shifted from pollutant monitoring in air, soil, and water toward personal exposure measurements and biomonitoring. This trend along with the paucity of health effect data for many of the pollutants studied raise ethical and scientific challenges for reporting results to study participants. Methods We interviewed 26 individuals involved in biomonitoring studies, including academic scientists, scientists from environmental advocacy organizations, IRB officials, and study participants; observed meetings where stakeholders discussed these issues; and reviewed the relevant literature to assess emerging ethical, scientific, and policy debates about personal exposure assessment and biomonitoring, including public demand for information on the human health effects of chemical body burdens. Results We identify three frameworks for report-back in personal exposure studies: clinical ethics; community-based participatory research; and citizen science 'data judo.' The first approach emphasizes reporting results only when the health significance of exposures is known, while the latter two represent new communication strategies where study participants play a role in interpreting, disseminating, and leveraging results to promote community health. We identify five critical areas to consider in planning future biomonitoring studies. Conclusion Public deliberation about communication in personal exposure assessment research suggests that new forms of community-based research ethics and participatory scientific practice are emerging.